Nanotechnological Advancements for the Theranostic Intervention in Anaplastic Thyroid Cancer: Current Perspectives and Future Direction - Uppalapati, Sai S.; Guha, Lahanya; Kumar, Hemant; Mandoli, Amit (Current Cancer Drug Targets, 2024)
Anaplastic thyroid cancer is the rarest, most aggressive, and undifferentiated class of thyroid cancer, accounting for nearly forty percent of all thyroid cancer-related deaths. It is caused by alterations in many cellular pathways like MAPK, PI3K/AKT/mTOR, ALK, Wnt activation, and TP53 inactivation. Although many treatment strategies, such as radiation therapy and chemotherapy, have been proposed to treat anaplastic thyroid carcinoma, they are usually accompanied by concerns such as resistance, which may lead to the lethality of the patient. The emerging nanotechnology-based approaches cater the purposes such as targeted drug delivery and modulation in drug release patterns based on internal or external stimuli, leading to an increase in drug concentration at the site of the action that gives the required therapeutic action as well as modulation in diagnostic intervention with the help of dye property materials. Nanotechnological platforms like liposomes, micelles, dendrimers, exosomes, and various nanoparticles are available and are of high research interest for therapeutic intervention in anaplastic thyroid cancer. The pro gression of the disease can also be traced by using magnetic probes or radio-labeled probes and quantum dots that serve as a diagnostic intervention in anaplastic thyroid cancer.
Keywords: nanoparticles